The Present Position of New Testament Theology - Scott, Ernest F. (Harvard theological review, 1913)
It is not a little significant that several books have appeared within the last year or two which deal with the subject of New Testament Theology in its whole extent. For a considerable time there has been a shrinking from this large enterprise, and the work of Holtzmann was allowed to maintain its place without serious competition. The attention of younger scholars has been more directed to the literary and historical criticism of the New Testament than to its theology; and while the theology has been by no means neglected, it has been discussed in many separate monographs rather than in works of a comprehensive nature. Now, however, we have the three books of Weinel, Feine, and Schlatter, appearing almost simultaneously, while the monumental work of Holtzmann is being reissued in a fully revised edition.